A leitura do gênero anúncio publicitário/publipost e a formação de leitores - Ribeiro, Nayara Claudia (2022)
In many school contexts, technologies are configured as challenging in teaching and learning practices. By understanding the production of languages also related to the same challenges, it is feasible to problematize the processes permeated in reading activities to meet the demands of social language practices. Thus, the present work elects as an object of study the teaching of reading multimodal/multisemiotic texts, specifically, of advertising genres and conveyed by digital influencers and youtubers as "publipost". Its general objective is to analyze the possibilities of using the publipost genre, in order to produce a teaching project, in order to contribute to the continuing education of teachers. In order to achieve the proposed objective, a priori, a theoretical research was carried out based on authors who deal with issues related to the Pedagogy of Multiliteracies (ROJO, 2009; 2012; 2013), to the Theory of Multimodality and to the Grammar of Visual Design (ROJO, 2009; 2012; 2013). DIONÍSIO, 2005; 2011; VIEIRA; SILVESTRE, 2015; KRESS; VAN LEEUWEN, 2006), to the advertisement genre and its persuasive character, in addition to the reading conceptions of some scholars. A posteriori, data analysis will take place from the assumptions guided by the National Common Curriculum Base (BNCC, 2018) and through a survey and selection of advertising campaigns that circulate in digital media. From the studies and verifications undertaken, a teaching project was built that covered a didactic sequence of activities aimed at Portuguese language classes in the 9th year of Elementary School II, which will be addressed through an extension course for undergraduate students and teachers of basic education. From the analysis, it was possible to perceive that the work with the publipost genre can contribute to the formation of the emancipated reader regarding consumerism. Therefore, it is expected that the research legitimizes itself as a contribution to the training of Portuguese Language teachers with the aim of mitigating and embracing the complexities of teaching the reading of new texts, in addition to enabling the development of the student capable of exercising a critical reading of the publiposts that circulate in their digital media.